1992
DOI: 10.1128/iai.60.4.1447-1454.1992
|View full text |Cite
|
Sign up to set email alerts
|

Influence of immunization on Porphyromonas gingivalis colonization and invasion in the mouse chamber model

Abstract: The effects of immunization with invasive or noninvasive Porphyromonas (Bacteroides) gingivalis strains on the pathogenesis of infection in a mouse chamber model were examined. BALB/c mice were immunized by a single injection of heat-killed P. gingivalis invasive strain A7436 or W83 or noninvasive strain 33277, HG405, or 381 directly into subcutaneous chambers. P. gingivalis-specific antibody was detected in chamber fluid 21 days postimmunization, and mice were subsequently challenged by injection of exponenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 45 publications
3
40
0
Order By: Relevance
“…It is also possible that, by repeated laboratory transfer, this strain lost the ability to express the K-antigen. In the present study, we did not find a K-antigen in strain HG405 as in the invasive strains, which supports the findings of Genco et al (2). The K3 type is represented by strain A7A1-28.…”
Section: Discussionsupporting
confidence: 92%
“…It is also possible that, by repeated laboratory transfer, this strain lost the ability to express the K-antigen. In the present study, we did not find a K-antigen in strain HG405 as in the invasive strains, which supports the findings of Genco et al (2). The K3 type is represented by strain A7A1-28.…”
Section: Discussionsupporting
confidence: 92%
“…Human antibody reactivity has been reported for 55-, 47-and 40-kDa surface proteins of P. gingivalis (13) and for 75-, 57-, 51-, 46-, 35-and 19-kDa outer membrane proteins of P. gingivalis (40). Genco et al (16) reported reactivity of immune mouse sera with 43-^ 33-, 29-to 31-and 13-to 16-kDa antigens of fl gingivalis. Human antibody reactivity with A. actinomycetemcomitans has been reported to be primarily with the serotype-specific antigen (6,42).…”
Section: Discussionmentioning
confidence: 99%
“…Animal models have been used to study the pathogenicity of mono-infections of periodontopathogens such as P. gingivalis (27,72,93,96,100). These stu-dies examined the effect of immunization with invasive and non-invasive strains of P. gingivalis in the clearance of organisms, healing of lesions and production of speci®c antibodies as well as protective or non-protective isotypes.…”
Section: Coinfection Studiesmentioning
confidence: 99%